Parliament's Role in Poverty Reduction Strategies - Kroon, Cindy; Stapenhurst, Rick (World Bank, Washington, DC, 2012)
Parliaments play a crucial role in improving governance and public service delivery. Those countries with strong parliamentary oversight have been able to shape policy directions and priorities. This article explores the growing role of parliaments in crafting poverty reduction strategy papers (PRSPs) since the process was first launched in 1999. Although the parliaments of many developing countries still have a long way to go before they will maximize their ability to strengthen the outcomes from country-level poverty reduction strategies (PRSs), the first decade of the poverty reduction strategy process has produced some important examples of the ways that parliaments can get involved, shape the debate, and learn from the experiences of legislatures in other countries. The cases of Tanzania and Malawi illustrate how parliamentary committees and parliaments can develop in terms of policy leverage and leadership.